MOTIVASI WISATAWAN KE CHINATOWN KABUPATEN SIAK - Ranto Wijaya; Andi M Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
In a study using this descriptive quantitative research method, there is a purpose to know the image of Chinatown Siak District tourist attraction. In addition, to find out the motivation of tourists visiting the tourist attraction Chinatown Siak District. And to know what are the constraints of tourists to visit Chinatown and how the Siak District Tourism Office will be done in the future. Based on the results of research that has been done Tourist attractions Chinatown is a tourist attraction that is basically a cultural attraction, because the area is interesting to be traced by tourists because it is still a strong culture of Chinese people in the region. According to the recapitulation of respondents' responses on the motivation of tourists to Chinatown, showed the cultural motivation to get the highest score with a total score of 1198 and the lowest score is social motivation with a score of 983. Physical motivation with a total score of 1084 and fantasy motivation get a total score of 1060. In addition, tourists get to come to Chinatown is still encountered such as, obstacles renovation of attractions, parking and other facilities that have not been adequate, until the absence of public transportation can be used by tourists to come to Chinatown. And the future Tourism Office efforts are to develop Chinatown objects and facilities, create weekly attractions, to form POKDARWIS, to coach local guides.Keywords: Motivation, Chinatown, tourists